The use of agonistic anti-CD40 therapy in treatments for cancer - Khong, A.; Nelson, Delia; nowak, A.; Lake, R.; Robinson, B. (Taylor & Francis, 2012)
Agonistic anti-CD40 antibody is a potent stimulator of anti-tumor immune responses due to itsaction on both immuneand tumor cells. It has the ability to “precondition” dendritic cells, allowingthem to prime effective cytotoxic T-cell responses. Thus, anti-CD40 antibody provides an idealtherapy for combination with traditional cancer treatments (i.e., chemotherapy, surgery) in orderto elicit immune-mediated anti-tumor effects. This review summarizes the mechanisms of actionof agonistic anti-CD40, the use of mouse models to investigate its effects and combinations withother therapies in vivo, and current clinical trials combining humanized anti-CD40 antibody withchemotherapy and/or other immunotherapies.